PENGARUH FIRM SIZE, AUDIT LAG, OPINI AUDIT TAHUN SEBELUMNYA DAN KUALITAS AUDIT TERHADAP OPINI AUDIT GOING CONCERN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2021) - Putri Azarya Greace; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
This research aims to test the influence of firm size, audit lag, debt default, firm size, prior-year audit opinion and audit lag on audit opinion going concerns in manufacturing companies The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2020-2021. The purposive sampling method is used as a sampling method with certain criteria with a total sample of 308 samples. Based on the results of the study showed that variable audit lag and prior-year audit opinion had an significant positive effect on the opinion of audit going concern. The firm size variable had a insignificant positive effect on the audit of opinion going concern. The acquisition of audit quality variables has a insignificant negative effect on the opinion of audit going concern.